Making waves. [article].
Competition for North Koreans' attention is increasing. The country's approved media are crammed with fawning reports about the latest "field guidance" from its dictator, Kimm Jong Un-indispensable tips on topics such as growing juicy apples or perfecting a nuclear weapon.
Keywords: Radio-Periodicals.; Radio in North Korea - Periodicals; Short wave radios - North Korea - Periodicals